Engineering colloidally stable, highly fluorescent and nontoxic Cu nanoclusters via reaction parameter optimization. Issue 27 (14th June 2022) - Busi, Kumar Babu; Kotha, Jyothi; Bandaru, Shamili; Ghantasala, Jyothi Priyanka; Haseena, Sheik; Bhamidipati, Keerti; Puvvada, Nagaprasad; Ravva, Mahesh Kumar; Thondamal, Manjunatha; Chakrabortty, Sabyasachi
Abstract : A facile synthetic strategy to engineer improved fluorescent quantum yield, colloidally stable, and low toxic Cu nanoclusters is introduced. These nanoclusters have the potential to be used as excellent bioimaging probes. Abstract : Metal nanoclusters (NCs) composed of the least number of atoms (a few to tens) have become very attractive for their emerging properties owing to their ultrasmall size. Preparing copper nanoclusters (Cu NCs) in an aqueous medium with high emission properties, strong colloidal stability, and low toxicity has been a long-standing challenge. Although Cu NCs are earth-abundant and inexpensive, they have been comparatively less explored due to their various limitations, such as ease of surface oxidation, poor colloidal stability, and high toxicity. To overcome these constraints, we established a facile synthetic route by optimizing the reaction parameters, especially altering the effective concentration of the reducing agent, to influence their optical characteristics. The improvement of the photoluminescence intensity and superior colloidal stability was modeled from a theoretical standpoint. Moreover, the as-synthesized Cu NCs showed a significant reduction of toxicity in both in vitro and in vivo models. The possibility of using such Cu NCs as a diagnostic probe toward C. elegans was explored. Also, the extension of our approach toward improving the photoluminescence intensity of the Cu NCs on other ligand systems was demonstrated.